Sweaty feet in adolescents: early use of botulinum type A toxin in juvenile plantar hyperhidrosis - Bernhard, Matthias K.; Krause, Matthias; Syrbe, Steffen (Pediatric dermatology, 2018)
Background/Objectives Plantar hyperhidrosis can have severe social effects on children and adolescents. Therapeutic options include antiperspirants and surgical interventions (eg, sympathectomy). Botulinum type A toxin is approved for axillary hyperhidrosis in adults only. The aim of the study was the determination of effect and safety of botulinum type A toxin in plantar hyperhidrosis in juvenile patients. Methods Children and adolescents with idiopathic focal plantar hyperhidrosis were treated with 50-100 U of botulinum type A toxin per sole. Local anesthesia was provided using topical eutectic mixture of local anesthetics cream and ice, in combination with midazolam as an anxiolytic. Results Fifteen patients (aged 12-17) were included in the study. Best results were achieved with a dose of 75-100 U of botulinum type A toxin per sole. Two patients did not benefit from the therapy, and 11 (73%) were satisfied with the results. Nine patients (60%) experienced pain at the injection site for a maximum duration of 3 days. One patient reported transient focal weakness for 4 weeks. Conclusion Botulinum type A toxin seems to be a safe secondary treatment option for plantar hyperhidrosis in adolescents aged 12 and older. A dose of 75-100 U per sole resulted in a good therapeutic effect of variable duration in most patients. There were no severe side effects.